Introduction to bioorganic chemistry and chemical biology - Van Vranken, David L.; Weiss, Gregory A. (Garland Science, 2013)
"Introduction to Bioorganic Chemistry and Chemical Biology integrates organic chemistry with biological concepts that are fundamental to biology, physiology, and medicine. This problems-driven textbook explains the chemical structures of biooligomers (genes, DNA, RNA, proteins, glycans, lipids, and terpenes) as the molecular engines for life. It then applies organic chemistry to examine the central dogma of molecular biology. Biological macromolecules are rendered to reveal secondary structure and modern depictions of organic structures and mechanistic arrow-pushing will be familiar to all students who have taken an introductory course in organic chemistry"-- Anotace vydavatele.
Terminologický slovník
Keywords: biochemie; bioorganická chemie; molekulární biochemie; biochemistry; bioorganic chemistry; molecular biochemistry; učebnice vysokých škol; textbooks (higher)